(untitled) (Sir Salimullah Medical College Journal, 2022)
Background: Spinal anaesthesia is widely used for transurethral resections of prostate (TURP) because it allows early recognition of symptoms caused by over hydration, TURP syndrome, and bladder perforation. Patients undergoing TURP surgery have coexisting pulmonary or cardiac disease. Objective: To evaluate the outcome of the two anaesthetic agents – levobupivacaine and bupivacaine in TURP surgery when they are combined with fentanyl. Method: Total eighty patients were selected by inclusion and exclusion criteria, and then the selected patients were randomly divided into 2 groups (40 in each). levobupivacaine group (1) was received intrathecal 0.5% levobupivacaine 5mg (1 ml) + 25 micro gram fentanyl (0.5ml) and in bupivacaine group (2) was received intrathecal 0.5% bupivacaine heavy 5 mg(1ml) +25 micro gram fentanyl(0.5ml) slowly @1ml/10sec. Heart rate, noninvasive systolic, diastolic and mean arterial blood pressures and oxygen saturation (SpO2) were recorded immediately before intrathecal injection and every 3 min for 15 min after intrathecal injection and there after every 5 minutes upto 40 minutes and at the end of surgery. Results: All the haemodynamic variables except heart rate were almost statistically matched. Half of levobupivacaine group and 30% of the bupivacaine group achieved a sensory block up to the level of T10. Sixty percent of the levobupivacaine and 15% of the bupivacaine group at the beginning of the surgery had modified Bromage score ‘1’. None of the levobuppivacaine and 15% of the bupivacaine groups had a Bromage score ’3’. The recovery from motor block was significantly earlier in the levobupivacaine group compared to that in the bupivacaine group. Over half (55%) of the former group exhibited complete recovery at the end of surgery as opposed to only 20% of the latter group. Conclusion: For TURP surgery, a low dose of levobupivacaine with fentanyl can provide an adequate sensory blockade and can be used as a good alternative to bupivacaine. Sir Salimullah Med Coll J 2022; 30: 115-122